ANALISIS KOMPETENSI PEDAGOGIK GURU MATA PELAJARAN EKONOMI KELAS X DI MAN 2 PONTIANAK - yarso, Fitri; Khosmas, F. Y.; Okianna, Okianna (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis study aims to determine the pedagogical competence of teacher in teaching economic subjects class X in Man 2 Pontianak. The Research method used is a descriptive method with a qualitative approach and survey research forms. The source of data in this study is the teacher of economic subjects class X in Man 2 Pontianak and dokumentation relating to teacher pedagogical competence. Data collection was obtained through observation guidelines and interview guidelines then analyzed using data reduction, data peresentation and verification/conclusion drawing. Then the validity of the data using triangulation thecniques.the researcher conducted the research by observing the study twice and interviewing for three days.the results showed that the pedagogical competence of class X economics teachers in Man 2 Pontianak as a whole was good, but still needed refinement on each indicator especially in the sub indicators applying strategies, methods and learning models that varied to increase student learning motivation, and sub indicators know the talent, interest and potential possessed by students. Keywords: Teacher’s Pedagogical competence, Class X Economic Subjects